Management of Unoperated Tetralogy of Fallot in a 59-Year-Old Patient - Robin Boyer MD; Hyung Jin Kim DO; Rajagopal Krishnan MD (SAGE Publishing, 2020)
Tetralogy of Fallot is the most common cyanotic congenital heart defect consisting of an overriding aorta, right ventricular outflow obstruction, ventricular septal defect, and right ventricular hypertrophy. Without surgical management, approximately only 3% of patients survive past the age of 40 years. Cases of unoperated patients reaching adulthood have been reported; however, few studies describe treatment guidelines for surgical or therapeutic management. In this article, we report the case of a 59-year-old Hispanic male with unoperated tetralogy of Fallot presenting to our cardiology clinic for initial workup and management.